Gastroesophageal Reflux and Idiopathic Pulmonary Fibrosis: A Review - Fahim, Ahmed; Crooks, Michael; Hart, Simon P. (Pulmonary Medicine, 2011)
The histological counterpart of idiopathic pulmonary fibrosis is usual interstitial pneumonia, in which areas of fibrosis of various ages are interspersed with normal lung. This pattern could be explained by repeated episodes of lung injury followed by abnormal wound healing responses. The cause of the initiating alveolar epithelial injury is unknown, but postulated mechanisms include immunological, microbial, or chemical injury, including aspirated gastric refluxate. Reflux is promoted by low basal pressure in the lower oesophageal sphincter and frequent relaxations, potentiated by hiatus hernia or oesophageal dysmotility. In susceptible individuals, repeated microaspiration of gastric refluxate may contribute to the pathogenesis of IPF. Microaspiration of nonacid or gaseous refluxate is poorly detected by current tests for gastroesophageal reflux which were developed for investigating oesophageal symptoms. Further studies using pharyngeal pH probes, high-resolution impedance manometry, and measurement of pepsin in the lung should clarify the impact of reflux and microaspiration in the pathogenesis of IPF.